The Financing of Graduate and Professional Education in Minnesota with Coordinating Board Recommendations. A Policy Paper - Minnesota Higher Education Coordinating Board, St. Paul.; Minnesota Higher Education Coordinating Board, St. Paul. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
Designed to assess the relationship of various state policies for postsecondary education to graduate and professional education, this report identifies principal financing issues for use in advising state policy-makers. An introductory section describes the background and approach of the study, findings and conclusions, recommendations (including the rationale and impact of each), and the background of graduate and professional education. Chapter II describes the nature of graduate and professional education and its costs. Chapter III analyzes the state's financial support for advanced study in Minnesota through the financing of institutions, programs and students. Chapter IV provides background on topics which provide perspective on financing graduate and professional education in Minnesota. Major developments shaping advanced study nationally are outlined in Chapter V. Conclusions about the appropriateness of state financing policies are presented in Chapter VI. Five tables provide data on funding, institutions, enrollments and degrees. The Board recommendations include continued unrestricted financing of systems; funding of graduate fellowships at the University of Minnesota; exploration of more creative ways to assist graduate and professional students in financing their education; and exploration for the establishment of guidelines for program outcomes. (KM)
ERIC Note: For related document, see HE 020 993.
Educational level discussed: Higher Education.
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Degrees (Academic); Doctoral Degrees; Educational Finance; Enrollment; Fellowships; Financial Policy; Full State Funding; Graduate Study; Higher Education; Masters Degrees; Postsecondary Education; Professional Education; State Aid; State Colleges; State Universities; Student Financial Aid; Tuition Grants; Minnesota; Reports, Descriptive